Rockfall hazards in Türkiye based on data up to the 2020 s - Tayfun Kurt (Discover Geoscience)
Abstract Rockfalls pose a significant threat to both human life and infrastructure in Türkiye, particularly in mountainous regions. This study conducts a comprehensive spatiotemporal analysis of fatal rockfall events over the past five decades. The findings reveal a widespread distribution of rockfalls across the country, with natural hazards such as heavy rainfall, earthquakes, and erosion identified as primary triggers. Moreover, human activities including unregulated construction and mining have exacerbated the risk of rockfalls. To mitigate the impacts of these events, the study emphasizes the need for enhanced risk assessment, early warning systems, and effective land-use planning. The results of this research provide valuable insights for policymakers and researchers seeking to reduce the vulnerability of Turkish communities to rockfall hazards.